Histochemical Analysis of Paraspinal Rotator Muscles From Patients With Adolescent Idiopathic Scoliosis: A Cross-Sectional Study. Issue 8 (February 2015) - Wajchenberg, Marcelo; Martins, Delio Eulalio; Luciano, Rafael de Paiva; Puertas, Eduardo Barros; Del Curto, David; Schmidt, Beny; Oliveira, Acary Bulle de Souza; Faloppa, Flavio
Abstract : Abstract: Morphological, biochemical, and histopathological alterations in the paraspinal skeletal muscle of patients with adolescent idiopathic scoliosis (AIS) have been extensively reported. We evaluated rotator muscle fibers from the apex vertebra of AIS patients through histological and immunohistochemical analysis. A population of 21 female AIS patients who underwent corrective surgery between 2010 and 2013 had biopsies taken from the paraspinal muscle in the convex and concave sides of the thoracic curve apical vertebra. Serial sections were stained following routine protocols for hematoxylin and eosin (HE), Sudan red, Gomori trichrome, NADH, ATPase, and cytochrome oxidase. We assessed muscular atrophy and hypertrophy, fatty proliferation, endomysial and perimysial fibrosis, the presence of hyaline fibers, mitochondrial proliferation, muscular necrosis, nuclear centralization, and inflammation. Two independent professionals evaluated the slices. The thoracic curves had an average Cobb angle of 68 degree. Comparative analysis of the concave and convex sides was performed with McNemar test at a significance level of 5%. Results showed significant differences in both endomysial and perimysial fibrosis and fatty involution between the two sides of the apex vertebra. Paraspinal muscles in the concave side of the scoliosis apex had significantly more fibrosis and fatty involution. However, both sides showed signs of myopathy, muscular atrophy due to necrosis, presence of hyaline fibers, and mitochondrial proliferation.